Experience of helmet usage among hearing aid users: a cross sectional study - Yuvaraj, Pradeep; E., Sinu; Parambath, Keerthana; Abubacker, Rahina; Rajasekaran, Aravind K. (International Journal Of Community Medicine And Public Health, 2023)
Background: In India, persons with hearing impairment who benefit from hearing aids can acquire a driving license. The law mandates helmet use while driving two-wheelers. Using a hearing aid with a helmet on may be a challenge, but it is paramount to understand the difficulties the hearing aid users face. Methods: A cross-sectional research design was used to study the experience of hearing aid users who ride two-wheelers. A checklist was developed and administered to 15 individuals with hearing impairment who ride two-wheelers. The checklist had 11 questions under three domains; ’helmet related,’ ’comfort related’, and ’driving/ listening related. The study was carried out in and around Bangalore. The data was collected through the interview method. Results: The subjects reported difficulties in the comfort-related and driving/listening-related domains. Many participants felt the need to modify the helmet design to suit hearing aid users. They also felt a need for a special program for driving mode in the hearing aids. Conclusions: Hearing-impaired two-wheeler riders face problems in localization, fear of hearing aid falling, and sweating using hearing aids while driving. It affects them on two fronts. One, it may pose a risk to others or the hearing impaired themselves on the road. Second, avoiding riding two-wheelers may limit their rights and mobility.